2020
DOI: 10.1097/shk.0000000000001713
|View full text |Cite
|
Sign up to set email alerts
|

Low Microcirculatory Perfused Vessel Density and High Heterogeneity are Associated With Increased Intensity and Duration of Lactic Acidosis After Cardiac Surgery with Cardiopulmonary Bypass

Abstract: and low MFIv. Conclusion: Low perfused vessel density and high microcirculatory heterogeneity are associated with an increased intensity and duration of lactic acidosis after cardiac surgery with cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…This study interpreted that CPB procedure altered microvascular perfusion, and anesthesia partially contributed to the alterations. Greenwood et al further demonstrated the association between impaired microcirculation and POHL in cardiac surgery with CPB [ 20 ], and the inflammatory responses played a role in POHL development [ 21 ]. Mini-CPB could lead to fewer alterations of microperfusion, and its use may clinically improve outcomes in patients with high-risk surgery and in those with longer procedures [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study interpreted that CPB procedure altered microvascular perfusion, and anesthesia partially contributed to the alterations. Greenwood et al further demonstrated the association between impaired microcirculation and POHL in cardiac surgery with CPB [ 20 ], and the inflammatory responses played a role in POHL development [ 21 ]. Mini-CPB could lead to fewer alterations of microperfusion, and its use may clinically improve outcomes in patients with high-risk surgery and in those with longer procedures [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The median lactic acid in our study was 3.6 ± 3.3 mmol/L before surgery and 5.0 ± 5.2 mmol/L after surgery. In our research, preoperative and postoperative lactic acid levels of patients with dissection under CPB were higher than those of other types of surgery 27 . The study of CPB in this paper is more detailed than that in previous papers.…”
Section: Discussionmentioning
confidence: 43%
“…Using data from our previous foundational work as well as unpublished pilot data, we anticipate a 1:1 allocation of patients to the high (PVD > 22mm/mm 2 ) and low group (PVD � 22 mm/mm 2 ). We will need a sample size of at least 134 subjects to detect at least a 2-day difference in ventilator and vasopressor-free days (VVFDs) with a β = 0.8, using a one-sided t-test α = 0.05 [5,6]. We will enroll a total of 140 subjects to allow for a 5% loss to follow-up (surgical delay, ICU delay, cancelled surgery, etc.)…”
Section: Sample Size and Powermentioning
confidence: 99%
“…Using these methods, previous literature has concluded that lactic acidosis after cardiac surgery is unlikely related to inadequate oxygen delivery [4]. Unfortunately these inferences fail to consider the presence of regional blood flow derangements caused by pathologic microcirculatory heterogeneity, which are also associated with severity of postoperative lactic acidosis and organ injury [5,6]. To resolve this important clinical discrepancy, a deeper understanding of the determinants of oxygen transport pathways and oxygen utilization during health, shock, and resuscitation are needed.…”
Section: Introductionmentioning
confidence: 99%